Evaluation of changes in the cognitive function of adult cynomolgus monkeys under stress induced by audio-visual stimulation by applying modified finger maze test - Huang, Ying; Wang, Hong; Yang, Chen; Luo, Yuchong; Ding, Yongyan; Jin, Hongjun; Wen, Shenglin (Frontiers in Neuroscience, 2022)
Stress in life is ubiquitous and unavoidable. Prolonged exposure to severe stress can lead to physical intolerance and impair cognitive function. Non-human primates are considered to be the best animal model for studying cognitive function, especially memory and attention. The finger maze test, with the advantages of short training time and lower cost, is recommended to evaluate learning and memory in non-human primates. In this study, we modified the finger maze test method to evaluate the cognitive function of single-housed cynomolgus monkeys. The flexibility and attention of cynomolgus monkeys were assessed by performing the complex task test and the stranger intrusion interference test, respectively, which increased the difficulty of obtaining rewards, and the ability of long-term memory was also evaluated by the memory test. Furthermore, the changes in cognitive function of the cynomolgus monkeys were tested by using the finger maze test after audio-visual stimulation, and the changes in the cortisol levels during stimulation were also analyzed. We found that, after completing the learning test, there was no significant decrease in their success rate when monkeys processed multitasks at the same time. In the stranger intrusion interference test, all subjects were distracted, but the accuracy did not decrease. The monkeys completed the memory tests in the 1st and 2nd months after the learning tests, with a high success rate. However, the success rate decreased significantly at the end of the 4th month. During audio-visual stimulation, the plasma cortisol level significantly increased in the first 2 months and was maintained at a high level thereafter. One month after audio-visual stimulation, the accuracy of the memory test was significantly reduced, and the total time of distraction was significantly prolonged. In conclusion, chronic audio-visual stimulation can increase blood cortisol levels and impair cognitive function. The modified finger maze test can evaluate many aspects of cognitive function and assess the changes in the cognitive function of adult cynomolgus monkeys under stress.